A membrane biofilm reactor for hydrogenotrophic methanation. (February 2021) - Pratofiorito, Giorgio; Hackbarth, Max; Mandel, Carmen; Madlanga, Siyavuya; West, Stephanie; Horn, Harald; Hille-Reichel, Andrea
Highlights: Direct feeding of substrate gases to the biofilm improves mass transfer of H2 . Total biofilm coverage of membranes proved possible and stable over time. Membrane bound biofilms allow for excellent controllability of product gas quality. Abstract: Biomethanation of CO2 has been proven to be a feasible way to produce methane with the employment of H2 as electron source. Subject of the present study is a custom-made membrane biofilm reactor for hydrogenotrophic methanation by archaeal biofilms cultivated on membrane surfaces. Reactor layout was adapted to allow for in situ biofilm analysis via optical coherence tomography. At a feeding ratio of H2 /CO2 of 3.6, and despite the low membrane surface to reactor volume ratio of 57.9 m 2 m −3, the maximum methane production per reactor volume reached up to 1.17 Nm 3 m −3 d −1 at a methane content of the produced gas above 97% (v/v). These results demonstrate that the concept of membrane bound biofilms enables improved mass transfer by delivering substrate gases directly to the biofilm, thus, rendering the bottleneck of low solubility of hydrogen in water less drastic.